Assessing Foliar Chlorophyll Content with SPAD-502 Chlorophyll Meter: A Comparison with Spectrophotometer Method in Various Plants - Nurbaiti, Siti; Milasari, Asri Fajar; Wibowo, Wiko Arif; Nilamsari, Elvian Indah; Rachmawati, Diah (Universitas Negeri Surabaya, 2025)
Measuring chlorophyll content in plants is one of the main points that has never been ignored in various plant biology and agronomy research studies. Chlorophyll content is a parameter of growth and development, diagnosis of nutritional status, and response to environmental conditions. This study aimed to compare and determine the relationship between SPAD-502 chlorophyll meter readings and chlorophyll content obtained from acetone extraction followed by spectrophotometry measurement. Various leaves with different colors and thicknesses were used to determine the reliability of SPAD readings across diverse morphological traits. The results showed higher SPAD readings in leaves with a greener color. SPAD value was found to have a good linear relationship (r 0.8 and R2 0.64) and a positive correlation with total chlorophyll content, though variations due to leaf thickness suggest the need for correction factors. Furthermore, SPAD has potential as a rapid, non-destructive tool for monitoring plant health and nutrient status in agriculture, plant breeding, and horticulture. This tool can contribute to optimizing crop yield and managing fertilization practice, especially where the maintaining leaf integrity is essential for both commercial and aesthetic value. Species-specific calibration models are recommended to enhance measurement accuracy.